STRENGTHENING MODEL FOR DAIRY CATTLE BREEDERS WITH PROFIT-SHARING SYSTEM IN TRENGGALEK REGENCY - Artini, Widi; Sidhi, Eko Yuliarsha; Lisanty, Nina; Sutiknjo, Tutut Dwi; Bahar, Asikin (Lampung University, 2025)
The Government of Trenggalek Regency is strongly committed to advancing the dairy cattle industry and boosting milk production in the region, with particular emphasis on Dompyong Village, Bendungan District. This research aims to assess the capital requirements for dairy cattle farming and develop a model to strengthen the position of breeders using a profit-sharing system. A survey method, incorporating both quantitative and qualitative descriptive approaches, was employed to gather comprehensive data. The study revealed that independent dairy cattle farming requires a total capital of IDR 23,150,000. However, under the profit-sharing system, breeders need only IDR 9,900,000 due to shared costs for purchasing dairy cows. The profit-sharing arrangement generally involves a 50:50 split between breeders and investors, including income from the sale of calves and milk, resulting in a total profit-sharing value of IDR 23,000,000 per year. Additionally, breeders receive 10 to 20 percent of the revenue from the sale of dairy cows, depending on the agreement. The proposed model for strengthening breeders focuses on developing their character and credibility to build investor trust, advocating for written profit-sharing agreements to prevent disputes, and enhancing institutional support to improve business efficiency and provide technical guidance. Keywords : dairy cows; livestock, profit-sharing system.